Selected aspects of philosophy in coaching: Reflexions on humanistic knowledge and the practice of coaching - Musioł, Anna Agnieszka (Folia Philosophica, 2021)
In this paper I undertake anattemptindication of dependences binding philosophy with coaching. Round the coaching grew many myths. Thereby in the paper I refer coaching as the present form of helping professions with the second man (with the customer/coachee); the profession whose method and the tool reach philosophical thought of different epochs, determining a permanent foundationunder the humanities. This foundation determines till now elaborate by thinkers the knowledge about the man, to his form and the place in the world. The reflection over philosophical aspects in coaching I begin from the description of chosen thoughts the ancient epoch in which the philosophy — accenting its own practical character — appears as art of living; across analysis of the meaning of Max Scheler and Nicolai Hartmann axiological ethics; finishing of the twentieth century eternal philosophy of dialogue.